2013
DOI: 10.1002/hep.25993
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reliability criteria for liver stiffness evaluation by transient elastography

Abstract: Liver stiffness evaluation (LSE) is usually considered as reliable when it fulfills all the following criteria: ≥10 valid measurements, ≥60% success rate, and interquartile range / median ratio (IQR/M) ≤0.30. However, such reliable LSE have never been shown to be more accurate than unreliable LSE. Thus, we aimed to evaluate the relevance of the usual definition for LSE reliability, and to improve reliability by using diagnostic accuracy as a primary outcome in a large population. 1,165 patients with chronic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
465
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(474 citation statements)
references
References 35 publications
4
465
2
3
Order By: Relevance
“…CAP values were considered valid when at least 10 measurements per assessment were obtained from which the final value was based on. LSM values were included in the analyses, if the interquartile range /median LSM was ≤ 30% for values < 7.1 kPa [29].…”
Section: Quantification Of Hepatic Steatosismentioning
confidence: 99%
“…CAP values were considered valid when at least 10 measurements per assessment were obtained from which the final value was based on. LSM values were included in the analyses, if the interquartile range /median LSM was ≤ 30% for values < 7.1 kPa [29].…”
Section: Quantification Of Hepatic Steatosismentioning
confidence: 99%
“…188 New reliability criteria for transient elastography have indicated that determinations of hepatic fibrosis are reliable (74%) or very reliable (17%) in 91% of assessments and poorly reliable in 9%. 189 Transient elastography has been similar to 190,191 or better than 192 APRI as a predictor of cirrhosis, and its performance has been similar to 190 (or possibly lower 193 than), the FibroTest for diagnosing the stages of fibrosis in chronic hepatitis C ( Table 3). The combination of ELF with transient elastography has increased the negative and positive predictive values of each test alone for the diagnosis of hepatic fibrosis stage ≥2 and cirrhosis.…”
Section: Transient Elastographymentioning
confidence: 98%
“…161 Comparative trials: Same or better than APRI for cirrhosis [191][192][193] Same or worse than FibroTest by stages 191,194 FibroTest and FibroScan match liver biopsy 191 Confirmed effective by four meta-analyses 179,[195][196][197] Predictive of 5-year survival in chronic HCV 162 Many non-fibrotic factors affect liver stiffness [201][202][203][204] Tested in chronic HCV 189,191,194 , HBV 198,199 Real-time elastography Measures echo displacement before and after liver compression and reconstructs strain field as reflective of tissue elasticity Spleen stiffness correlates with varices 217,218 Many non-fibrotic factors affect liver stiffness 221,225 Tested in diverse chronic liver diseases 209 APRI, aspartate aminotransferase/platelet ratio index; ARFI, acoustic radiation force impulse imaging; AST, serum aspartate aminotransferase level; HBV, hepatitis B virus; HCV, hepatitis C virus.…”
Section: Transient Elastographymentioning
confidence: 99%
“…A successful examination was defined as 10 validated measurements and an interquartile range (IQR) to median ratio of ≤30% [14]. The standard medium (M)-probe was used for all patients, with a frequency of 3.5 MHz and a measurement depth of 25 to 65 mm.…”
Section: Measurements and Study Proceduresmentioning
confidence: 99%